The disrupted balance between hair follicles and sebaceous glands in Hoxc13‐ablated rabbits. Issue 1 (20th August 2018) - Deng, Jichao; Chen, Mao; Liu, Zhiquan; Song, Yuning; Sui, Tingting; Lai, Liangxue; Li, Zhanjun
ABSTRACT: Pure hair and nail ectodermal dysplasia 9 (ECTD‐9) is an autosomal recessive genetic disease caused by mutation of HOXC13 and is characterized by hypotrichosis and nail dystrophy in humans. Unlike patients with ECTD‐9, Hoxc13 ‐mutated mice and pigs do not faithfully recapitulate the phenotype of hypotrichosis, so there is a limited understanding of the molecular mechanism of Hoxc13 ‐mediated hypotrichosis in animal models and clinically. Here, the homozygous Hoxc13 −/− rabbits showed complete loss of hair on the head and dorsum, whereas hypotrichosis in the limbs and tail were determined in the Hoxc13 −/− rabbits. In addition, reduced hair follicles (HFs) while the enlarged and increased number of sebaceous glands (SGs) were also found in the Hoxc13 −/− rabbits, showing that the disrupted balance between HFs and SGs may respond to hypotrichosis of ECTD‐9 in an animal model and clinically. Therefore, our findings demonstrate that Hoxc13 −/− rabbits can be used as a model for human ECTD‐9, especially to understand the pathologic mechanism of hypotrichosis. Moreover, the disrupted balance between HFs and SGs, especially in the Hoxc13 −/− rabbits, can be used as an ideal animal model for dermatology ailments, such as acne and hypotrichosis, in preclinical studies.—Deng, J., Chen, M., Liu, Z., Song, Y., Sui, T., Lai, L., Li, Z. The disrupted balance between hair follicles and sebaceous glands in Hoxc13 ‐ablated rabbits. FASEB J. 33, 1226–1234 (2019). www.fasebj.org